Intra-articular lipoma of the knee joint in a girl - Yilmaz, E; Karakurt, L; Akpolat, N; Özdemir, H; Belhan, O; Incesu, M (W B Saunders Co, 2005)
Intra-articular lipoma is a rare benign mass that commonly occurs in the knee joint. We present the case of a 15-year-old girl with a slowly growing mass in her right knee. There was no history of trauma. The patient had no catching, locking, or giving way of the knee. On magnetic resonance imaging, multiple fibrous septa within a hyperintense mass was determined. After the arthroscopic examination, complete resection by open surgery was performed. There was no tumor recurrence at the end of the 1-year follow-up period. True intra-articular lipoma should be distinguished from lipoma arborescens, which is a similar but more common condition.
Keywords: lipoma; knee joint; magnetic resonance imaging